2004
DOI: 10.1073/pnas.0405312101
|View full text |Cite
|
Sign up to set email alerts
|

A crucial arginine residue is required for a conformational switch in NifL to regulate nitrogen fixation in Azotobacter vinelandii

Abstract: NifL is an antiactivator that tightly regulates transcription of genes required for nitrogen fixation in Azotobacter vinelandii by controlling the activity of its partner protein NifA, a member of the family of 54 -dependent transcriptional activators. Although the C-terminal region of A. vinelandii NifL shows homology to the transmitter domains of histidine protein kinases, signal transduction between NifL and NifA is conveyed by means of proteinprotein interactions rather than by phosphorylation. Binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…steady-state level of nifH mRNA is not altered in the glnE mutant strain in the absence of added ammonium, we infer that there is sufficient 2-OG under nitrogen-limiting conditions in the mutant strain to saturate the 2-OG binding site on NifA, hence relieving inhibition by NifL (34,35). This sophisticated metabolic control of NifA activity facilitates the coupling of NH 4 ϩ production by nitrogenase to NH 4 ϩ assimilation, thus preventing the toxic consequences of glutamine overproduction observed when the glnE mutant strain is grown in the presence of external NH 4 ϩ .…”
Section: Figmentioning
confidence: 81%
“…steady-state level of nifH mRNA is not altered in the glnE mutant strain in the absence of added ammonium, we infer that there is sufficient 2-OG under nitrogen-limiting conditions in the mutant strain to saturate the 2-OG binding site on NifA, hence relieving inhibition by NifL (34,35). This sophisticated metabolic control of NifA activity facilitates the coupling of NH 4 ϩ production by nitrogenase to NH 4 ϩ assimilation, thus preventing the toxic consequences of glutamine overproduction observed when the glnE mutant strain is grown in the presence of external NH 4 ϩ .…”
Section: Figmentioning
confidence: 81%
“…Inhibition of Ti plasmid conjugative transfer by TraM joins a growing list of prokaryotic regulatory systems involving an activator-antiactivator complex, including NifA-NifL regulation of nitrogen fixation in Azotobacter vinelandii (33) and Klebsiella pneumoniae (34), ComK-MecA-ClpC regulation of competence in Bacillus subtilis (35), GcvA-GcvR regulation of oxidative cleavage of glycine (36), and CRP-CytR regulation of many operons in E. coli (37). In the cases of NifA-NifL and ComKMecA, the antiactivator binds to and titrates the activator, thus preventing DNA binding and transcriptional activation (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of NifA-NifL and ComKMecA, the antiactivator binds to and titrates the activator, thus preventing DNA binding and transcriptional activation (33)(34)(35). However in the cases of GcvA-GcvR and CRP-CytR, the antiactivator and the activator bind promoter DNA in tandem, and the interactions between the antiactivator and the activator at the promoter inhibit transcriptional activation (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions of Arg-306 cause NifL to constitutively inhibit NifA irrespective of environmental cues. We have demonstrated that the phenotype of one such mutation, R306C, is associated with a conformational change that apparently locks NifL in a form similar to the oxidized "on" state so that the mutant NifL protein inhibits NifA even under conditions appropriate for nitrogen fixation (20). We observe that some mutations in the GHKL domain of NifL that substantially reduce ADP binding suppress the phenotype of the R306C mutation.…”
mentioning
confidence: 82%
“…Section 1734 solely to indicate this fact. 1 changes required to inhibit NifA (20). The key role of arginine 306 in signal transmission has prompted us to investigate the role of other residues of the H domain of NifL in signal propagation.…”
mentioning
confidence: 99%